Human Travelling and COVID-19 Pandemic - Ruksakulpiwat, Suebsarn; Zhou, Wendie; Chiaranai, Chantira; Vonck , Jane E. (Siriraj Medical Journal, 2021)
Objective: To determine whether there is a relationship between the extent of human travel and the number of COVID-19 cases in Thailand. Materials and Methods: The data set on monthly COVID-19 in Thailand between January and July 2020 were retrieved from the Ministry of Public Health, Thailand. Data regarding people’s travel in Thailand during the COVID-19 pandemic and for the same period of 2019 were retrieved from Open Government Data of Thailand. A paired t-test was used to compare the differences between the number of journeys made in each mode of transport in 2019 (January - July) and 2020 (January - July). Pearson’s product-moment correlation coefficient was used to examine the relationships among studied variables. Results: A Paired Samples t-test showed that from January until July 2020, the number of journeys made by public buses, ships, and airplanes declined by more than 50% from the previous year (p < 0.05). Pearson correlation coefficients showed that the mean monthly number of COVID-19 cases was significantly and inversely correlated with the number of public bus journeys made (r = -0.897, p < 0.01), the number of train journeys (r = -0.834, p < 0.05), ship journeys (r = -0.890, p < 0.01), and airplane journeys (r = -0.911, p < 0.01). There was no significant relationship between the number of COVID-19 cases and private car journeys (r = -0.405, p = 0.367). Conclusion: During the pandemic, the number of journeys has been decreased. Moreover, the correlation between the number of journeys and COVID-19 cases has been shown in our analysis.